A magyar társasági jog modernizálása az 1930. évi V. törvénycikkben különös tekintettel a korlátolt felelősségű társaságokra - Ferencz, Barnabás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Ödön Kuncz’s proposal was adopted by the Hungarian Parliament in the form of Act V of 1930, as the reception of the limited liability company into Hungarian company law. The concept of Kuncz was based on criticism of the earlier bills of Dávid Pap and Géza Bozóky, and the experiences of jurisdictions that had already been adopted the German GmbH model, and it was in line with the needs of domestic business practice. This study analyses the reception of legal institution of limited liability company into Hungarian law and its medium-term effects based on the concept drawn up by Kuncz.